The concept of acquisition Its kinds and distinguish it from a like concept - الموسوي, علي فوزي; العامري, اندلس حامد (Journal of Legal Sciences, 2019)
This matter demands protecting economy from the acquisition on it by the holding companies with their influential impacts as a willingness to dominate and control the other companies which could lead to the disruption of the principle of equality among the shareholders in the financial and administrative rights because some persons follow several methods of control over the activity of the acquisition- targeted companies  and the confiscation of the rights of others resulting in a negative impact if accompanied by a lack of transparency and disclosure by holding companies. The holding company, whether directly or indirectly, may control a company's administration or other companies' administration leading to expansion in acquisition. This may result in narrowing the range of competitiveness among the companies or preventing the achievement of  fair competition among themselves.In the absence of the explicit provision in the Iraqi Companies Law No. 21 of 1997 as amended by the dissolved order from Coalition Provisional Authority (CPA) No. 64 for the year 2004, Iraqi legislator implied "acquisition. Nevertheless, what helped us in that was the legal Interim Iraq Stock Exchange No. 74 of 2004 and the Iraqi banks No. 94 for the year 2004 in reference to it. The legislator has pointed explicitly to the acquisition among banks. However, we need to seek some legal paragraphs for the full comprehension of subject knowledge. Therefore, the drafting of legal texts may deal with the Acquisition activity between banking and non-banking companies is indispensable.